Creativity, play and transgression: children transforming spatial design - Birch, Jo; Parnell, Rosie; Patsarika, Maria; Šorn, Maša (CoDesign, 2017)
Spatial designers, who engage children in their design process, most often frame children in this context as experts in their own lives. Findings from a study based at the University of Sheffield, point to new understandings of this participatory role, in which children move towards the role of designer. Drawing on interviews including visual methods with 16 spatial designers and guided by phenemonography, the paper seeks to represent the designers' perspectives on the under-explored area of child-designer interactions. Findings suggest that the designers understand these interactions to comprise a reciprocal and co-created space - a sphere of behaviours, actions and ways of being which together becomes an enabler of change. It is proposed that what Bhabha (The Location of Culture, 1994) refers to as a 'Third Space' in which the 'dominant culture might be temporarily subverted and its structural systems of power and control renegotiated' can be re-imagined in this co-design context. The paper weaves together theoretical discourse and empirical illustrations of perceived creativity, play and transgression, which - at their intersection - support a potential transformation of understandings of children as co-designers and of the design process itself.